Detrimental contribution of the immuno-inhibitor B7-H1 to rabies virus encephalitis (2008)
Rabies virus is the etiological agent of an acute encephalitis, which in absence of post exposure treatment is fatal in almost all cases. Virus lethality rests on its ability to evade the immune response. In this study, we analyzed the role of the immuno-inhibitory molecule B7-H1 in this virus strategy. We showed that in the brain and spinal cord of mice, rabies virus infection resulted in significant up-regulation of B7-H1 expression, which is specifically expressed in infected neurons. Correlatively, clinical rabies in B7-H1−/− mice is markedly less severe than in wild-type mice. B7-H1−/− mice display resistance to rabies. Virus invasion is reduced and the level of migratory CD8 T cells increases into the nervous system, while CD4/CD8 ratio remains unchanged in the periphery. In vivo, neuronal B7-H1 expression is critically depending on TLR3 signaling and IFN-β, because TLR3−/− mice—in which IFN-β production is reduced—showed only a limited increase of B7-H1 transcripts after infection. These data provide evidence that neurons can express the B7-H1 molecule after viral stress or exposure to a particular cytokine environment. They show that the B7-H1/PD-1 pathway can be exploited locally and in an organ specific manner—here the nervous system—by a neurotropic virus to promote successful host invasion.